Comparative study of perioperative morbidities of the conventional and ultrasound-guided suprapubic catheterization in the patients of urinary retention during emergency - Chandra, Mahesh; Parmar, Keyur; Wasnik, Seema (International Journal of Research in Medical Sciences, 2019)
Background: Urinary retention is one of the common urological emergencies and conventional ‘blind’ SPC frequently used comfortable as well superior procedure for patients. During conventional SPC, the distended bladder is identified by palpation or percussion without proper attention to intervening bowel segment and other structures. However, the recently published data suggests that if, ultrasound is used during SPC, and it identifies not only bladder but also intervening bowel segment which complications. Therefore, the objective of this study was to assess and compare the perioperative complications of both methods. Methods: This prospective study was conducted between years November’2017 to June’2019. Sixty patients (n=60) of urinary retention were randomized to undergo ultrasound guided or conventional SPC procedures. Patients were divided into two equal groups of 30 patients in US-SPC (Group-A) and C-SPC (Group-B). After either SPC, the patients were closely observed for development of complications. Results: Overall, the patients had mean age of 53.87+21.418 and 53.87+21.418 years in C-SPC and US-SPC group, respectively. Mean operative time and subsequent initial urine drainage were almost equal in both groups. However, in C-SPC group, 5(16.7%) patients developed complications in the form of 03 misplaced catheters outside bladder, 01 into retro pubic space and another 01 into rectum. All patients in Group-A required ultrasound guided revision of SPC compared to none in Group-B. Conclusion: Overall, the ultrasound-guided SPC (US-SPC) is safer procedure compared to conventional ‘blind’ C-SPC in relieving urinary retention in emergency, thus it should be recommended procedure whenever need arise for SPC procedure.